Radioprotection of beta-carotene evaluated on mouse somatic and germ cells - Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, Lúcia Regina [UNESP]; Xiao, Y.; Boei, J. J.; Natarajan, A. T. (Elsevier B.V., 1996)
In the present paper, the protective effect of beta-carotene was evaluated after whole body exposure of mice to 2 Gy of X-rays. Splenocytes, reticulocytes, bone marrow cells and spermatids were evaluated for the frequency of micronuclei (MN) induced by X-rays. Mice were treated (gavage) with beta-carotene (10, 25 and 50 mg/kg b.w.) for 5 consecutive days and, 4 h after the last treatment, the animals were irradiated. The results obtained showed different frequencies of X-ray-induced-MN between different cell populations analysed and also different response of these cells to the beta-carotene treatment. The radioprotective effect of beta-carotene was observed in splenocytes, reticulocytes, and spermatids but not in bone marrow cells. No dose-response relationship for beta-carotene was detected. The time of sampling, the sensitivity of the cells as well as the antioxidant activity of beta-carotene are discussed as important factors for the radioprotective action of this provitamin.
Keywords: beta-carotene; radioprotectors; antimutagenicity; micronucleus